(untitled) (Global Journal of Science Frontier Research, 2015)
Gmelina arborea Roxb is a major income earner for the Government and people of Cross River State, Nigeria. In spite of the vast economic potential of this plant in Nigeria, very little pathological research had been done on diseases afflicting this valuable species. In view of this, a survey on mycoflora and diseases associated with G. arborea was carried out in major plantations in Oban and Awi in Akamkpa Local Government Area and Ovonum in Obubra Local Government Area of Cross River State, Nigeria. Twenty four plant stands were sampled in four sites per location. The plant stands were examined for various disease symptoms and the means of infection calculated in each location. Percentage frequencies (occurrence) were also determined using the means. Randomized Block Design (RBD) was used for the experiment. A total of twenty fungi were isolated (root, bark, leaf, seed and soil) while five fungal diseases were identified in the field. The fungal isolates were: Aspergillus flavus, Aspergillus niger,